2020
DOI: 10.3390/ijms21072599
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cytogenetic Analysis in Freshwater Prawns of the Genus Macrobrachium (Crustacea: Decapoda: Palaemonidae)

Abstract: Freshwater prawns of the genus Macrobrachium are one of the important components of circumtropical marine, estuarine, and freshwater environments. They have been extensively exploited for human consumption for many years. More than 250 species reflect the evolutionary success of this highly diversified group, with a complex and challenging taxonomy due to morphological variations and vast geographical distribution. Although genetic approaches have been used to clarify phylogenetic and taxonomic aspects of Macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…A previous study [ 52 ] reported that the haploid number of chromosomes in oriental river prawn is 52. Other Macrobrachium species with reported karyotype analysis include the giant freshwater prawn ( Macrobrachium rosenbergii ; n = 59) [ 53 ], Dimua river prawn ( Macrobrachium villosimanus ; n = 62) [ 54 ], Macrobrachium siwalikensis (n = 50) [ 55 ], Lachester freshwater prawn ( Macrobrachium lachesteri ; n = 58) [ 56 ], freshwater shrimp ( Macrobrachium carcinus ; n = 47) [ 57 ], Macrobrachium acanthurus (n = 49) [ 57 ], and Amazon river prawn ( Macrobrachium amazonicum ; n = 49) [ 57 ]. In the present study, a total of 49 chromosomes were assembled, which is close to the reported number of haploid chromosomes in the oriental river prawn.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study [ 52 ] reported that the haploid number of chromosomes in oriental river prawn is 52. Other Macrobrachium species with reported karyotype analysis include the giant freshwater prawn ( Macrobrachium rosenbergii ; n = 59) [ 53 ], Dimua river prawn ( Macrobrachium villosimanus ; n = 62) [ 54 ], Macrobrachium siwalikensis (n = 50) [ 55 ], Lachester freshwater prawn ( Macrobrachium lachesteri ; n = 58) [ 56 ], freshwater shrimp ( Macrobrachium carcinus ; n = 47) [ 57 ], Macrobrachium acanthurus (n = 49) [ 57 ], and Amazon river prawn ( Macrobrachium amazonicum ; n = 49) [ 57 ]. In the present study, a total of 49 chromosomes were assembled, which is close to the reported number of haploid chromosomes in the oriental river prawn.…”
Section: Discussionmentioning
confidence: 99%
“…Large AT-rich probable HSs positioned in the (peri)centromeric position on all chromosomes and interstitially on some chromosomes suggest a high amount of repetitive DNA in the genome of P. leptodactylus (this study; Mlinarec et al, 2011 ). Large (peri)centromeric HSs have been found in different crustacean families such as Astacidae (Mlinarec et al, 2011 , 2016 ), Nephropidae (Deiana et al, 1996 ; Coluccia et al, 2001 ; Salvadori et al, 2002 ), Scyllaridae (Deiana et al, 2007 ), Palinuridae (Coluccia et al, 1999 , 2005 ; Cannas et al, 2004 ), Cambaridae (Salvadori et al, 2014 ), and Palaemonidae (González-Tizón et al, 2013 ; Torrecilla et al, 2017 ; Molina et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the hermit crab Pagurus pollicaris , a minisatellite AGTGCAG(CTG) n constitutes a large fraction of its genome (Chambers et al, 1978 ). An exceptional abundance of microsatellite and SSR sequences has also been found in the genome of freshwater prawns of the genus Macrobrachium (Palaemonidae) as well as in the penaeid shrimp Litopenaeus vannamei (Zhang et al, 2019 ; Molina et al, 2020 ), suggesting that short tandem repeats are a significant component of decapod crustaceans genomes.…”
Section: Discussionmentioning
confidence: 99%
“…The high diversity and worldwide tropical-subtropical distribution of Macrobrachium , combined with the scarcity of morphologic characters for accurate generic and specific delimitation, has long been intriguing taxonomists regarding its systematics, phylogenetic affinities, and biogeographic patterns. Several studies have been published on these topics using both morphological and molecular data, and, more recently, applying integrative approaches ( Pereira 1997 ; Bowles et al 2000 ; Murphy and Austin 2003 , 2005 ; Short 2004 ; Hernández et al 2007 ; Liu et al 2007 ; Valencia and Campos 2007 ; Wowor and Ng 2007 ; Parhi et al 2008 ; Wowor et al 2009 ; Pileggi and Mantelatto 2010 ; Acuña Gómez et al 2013 ; Rossi and Mantelatto 2013 ; Pileggi et al 2014 ; Jose et al 2016 ; Jose and Harikrishnan 2019 ; Mokambu et al 2019 ; Molina et al 2020 ). Among other factors, the high number of species has been hampering a comprehensive study on the phylogeny of the genus, but several articles were published on this at a regional level, either based on American (e.g., Pileggi and Mantelatto 2010 ; Acuña Gómez et al 2013 ; Rossi and Mantelatto 2013 ; Pileggi et al 2014 ), African (e.g., Mokambu et al 2019 ), or Indo-West Pacific species (e.g., Murphy and Austin 2005 ; Liu et al 2007 ; Parhi et al 2008 ; Chen et al 2009 ; Wowor et al 2009 ; Jose and Harikrishnan 2019 ; Siriwut et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%